Leprosy Health Promotion during COVID-19 Pandemic in Indonesia - Rahayu, Tri; Wicitra, Anindita; Lestari, Yeni Dwi; Irawati, Yunia; Bani, Anna Puspitasari; Andayani, Gitalisa; Susiyanti, Made; Daniel, Hisar; Puspitasari, Sitha Anisa (Faculty of Medicine, Public Health, and Nursing, Universitas Gadjah Mada, 2024)
Introduction: The COVID-19 pandemic has forced many conventional -face-to-face health promotion events to be conducted in an adaptive manner to keep healthcare in promotion, prevention, and even curative measures delivered to healthcare providers and patients. The same applies to leprosy, where Indonesia is still ranked as the third largest country with leprosy burden. This study aims to give rise to newer methods of health promotion on leprosy during this COVID-19 pandemic. Methods: Online training and case presentation workshop in the form of a KATAMATAKU webinar [MOU1] and live streaming via YouTube were held in August 2020. There were 120 general practitioners, 30 nurses, and 35 healthcare providers who registered and joined this event.[MOU2] Pre- and post-test [MOU3] were conducted to evaluate the participants' knowledge about the topics lectured during this training[MOU4] . Pre- and post-test were conducted using an online form, and all participants needed to answer several questions from each session. Participants were evaluated before the webinar began and after all sessions. We assessed the different scores from the pre- and post-test. Results: In the general practitioner group, median scores were 68 (27 – 95) and 82 (50 – 100) for pre- and post-test scores, respectively, with a mean difference between post and pre-test of 14.23+9.72. In nurses and other health care providers, the median for the pre-test score was 56 (22-89), and the post-test was 72 (39 – 100), with a mean difference between the post and pre-test of 18.93+10.27. Conclusion: In the pandemic situation, online seminars can be chosen as an effective method for health promotion to increase health care provider's knowledge. Pre- and post-test can be performed to evaluate participant's knowledge after the training. Regular training using online methods can be held in order to maintain participants' knowledge. We hope it can impact all health providers to continue their participation in the management of leprosy.